(untitled) (Acta Scientiarum. Health Sciences, 2012)
The experience of a family with a chronic disease is, at first, difficult and stressful, making the family unsafe and concerned. We aimed to understand the experience and adaptation of the family to a chronic illness (stroke) and describe the actions developed by a project of assistance at home. This is a qualitative study, Case Study type, conducted with a family assisted through home visits by the Project for Assistance and Support for the Family of Chronic Patients at Home, in Maringá, Paraná State. Data were gathered through consultation of the records of the family in May and June 2009, and data were submitted to content analysis. In the beginning there were many difficulties, however, over time the caregivers provided proper assistance, not considering it an obligation, but incorporating the situation to their normal routine, and they proved to be formidable in the process of care to patients, performing procedures with great skill, commitment and immeasurable love, affection and dedication. Accordingly, the responsibility of a health care professional is to intervene by providing appropriate guidance to the family, assisting in the rehabilitation of the family facing the care to this new condition.